Respiratory health of the small scale dairy workers of urban Bhubaneswar, Odisha - Singh, Snigdha; Kar, Sonali; Mishra, Alpana; Pattnaik, Dipti (Indian Journal of Community Health, 2022)
Background: Human in close inhabitation with the cattle due to unventilated or inadequately ventilated establishments or inadequate living space, is always at a risk of sustaining infection from the cattle through different modes of disease transmission. This study hints at the increased incidences in respiratory infections among dairy workers in unorganized and small scale dairy farms due to amendable unhygienic practices. Methods: This survey was part of a larger study, conducted after ethics approval. Number of households involved in dairy work surveyed were 60. From every house, two members actively involved in dairy work were chosen and total respondents were 120. The study tool was a semi structured, mixed questionnaire. Results: 67.5% dairy workers self-reported occurrence of respiratory symptoms which included the complaints like cough,breathing difficulty on exertion. None of the dairy workers were vaccinated against any milk borne disease.Conclusion: The housing, civic amenities accessed by them and their awareness are probably the main reasons for wide variety of self perpetuated practices and deviations of standard requirement.Use of protective gear (gloves,caps,masks) should be strictly emphasized and popularized.